Relevansi Jenis Teks Sastra Di Buku Pelajaran Dengan Kurikulum 2013 Dan Muatan Pendidikan Karakternya - Febriliani, Ariski (2016)
This tesearch aimed at describing the kind of literary texts in the textbook "Bahasa Indonesia Wahana Pengetahuan" class VIII Curriculum 2013 , describing the relevance of the kind of the literary texts with the competence of curriculum 2013, and the content of the character education. This research was a qualitative research. The data used in this research were literary texts. The techniques of data collection were observing and taking a note. The validity of data used the theory triangulation. The technique of data analysis used was content analysis or content study and comparation. The results of the research were: (1) Kind of the literary texts containing in the textbook were fable story, poem, script of a play, and short story. (2) The relevance of teaching material of the literary texts on the Core Competence (KI) of Curriculum 2013 was as much as 87,5% and on the Basic Competence (KD) of Curriculum 2013 was as much as 90,625%. (3) The content of character education values in the the literary texts of the textbook had 17 character education values of 18 character education values released by the Ministry of National Education, they were: (1) religious, (2) honest, (3) tolerant, (4) discipline, (5) hard work, (6) creative, (7) self-help, (8) democratic, (9) curious, (10) patriotism, (11) nationalism, (12) respecting the achivement, (13) friendly/communicative, (14) loving peace, (15) caring the environment, (16) social care, (17) responsibility. Only the value of being delight in reading that was not present in the literary texts.